Implant design based on imaging technique case study: skull reconstruction - Maya, Genisa; Abdullah, Johari Yap; Shuib, Solehuddin; Rajion, Zainul Ahmad (Springer, 2024)
Whether brought on by specific diseases, inherited traits, or trauma like an acci-dent, craniofacial surgery on the bones of the head or face is frequently necessary to manage these conditions. Sometimes it is necessary to remove a portion of the bone and replace it with implants, both for cosmetic and functional anatomical reasons. In addition to symmetrical (aesthetic) goals and functional maintenance, this missing bone reconstruction necessitates extra attention and is highly custom-ized. This research intends to describe how imaging techniques can be utilized to assist in designing an implant in a case study of a patient with cancer, where skull restoration is the choice of treatment. Based on image processing with MIMICS software, a three-dimensional (3D) computed tomography (CT) picture was used and processed to reconstruct the skull. The outcome demonstrated that the planned implant, produced by mirroring the tissues and Boolean operations, could close the hole in the cancer-related skull